Uso de Anticonceptivos en mujeres en edad fértil distrito de Juan Guerra – Región San Martín 1994 - Castro Hernández, Teresa (1994)
In the context of crisis, poverty and social unrest no attention to the issue of population is provided, or to demographic changes that are occurring much less take into account developments that have in the future and its representations as a source of social demands health. The issue of women's health is closely related to the problem of family planning, fertility, education, employment status, access to health services among others, so study them in our environment is necessary, so it is obvious that most health problems affecting these groups are aggravated by reproductive risk factors likely to be controlled with proper and rational use of family planning services. In general, developed countries are actively seeking new strategies in order to increase the availability of services and products for Family Planning, within a perspective of responsible parenthood that allows them to freely and consciously determine the number of children, guaranteeing quality of living (adequate nutrition, education, housing and employment status). The district Juan Guerra is located in the province of San Martin, department of the same name to 12 km., From the city of Tarapoto, Juanjui road, between the valleys of the rivers Cumbaza and May, with a population of 2799 approximately inhabitants according to the 1993 census, (whose main activities are agriculture and livestock). JUAN DISTRICT OF WAR - - REGION SAN MARTIN 1994, it focuses sociocultural characteristics, and trends of fertility regulation in all these precedents Given the expectation of knowing the CONTRACEPTIVE USE IN WOMEN AGE generated FERTIL women 15-49 years to guide programs in health and family planning. The increased use of modern contraceptive methods is still slow, nationally in 1986 was 28% in 1992 reached 33.5% figures. internationally, Colombia shows the highest figures 66%, 24% Bolivia, Ecuador 29%, Venezuela 32% being higher demand in urban than rural areas.